Comparison of cone beam-computed and micro-computed tomography data for measuring facial canal dehiscence - Mert Ocak; Ferhat Geneci; Bilge İpek Torun; Mehmet Fatih Şentürk; Emine Şebnem Kurşun Çakmak (Head & Face Medicine)
Abstract Background Selecting the correct imaging technique for critical anatomical structures is essential in descriptive studies and for supporting clinical applications. Facial canal dehiscence poses a significant risk for iatrogenic facial nerve injuries during middle ear surgeries. Accurate imaging is critical for surgical planning and minimizing complications. Detection of facial canal openings in the clinic is performed using imaging methods such as high-resolution computed tomography (HRCT). Studies have shown that the sensitivity of this method is approximately 66%. A high-resolution, 3D imaging method was used to measure the sensitivity of HRCT in the most accurate way. Aims/Objectives This study aimed to compare two radiological methods for measuring facial canal dehiscence. Specifically, we compared cone-beam computed tomography (CBCT) with high-resolution micro-computed tomography (micro-CT). Materials and methods Thirty-six temporal bone specimens without external defects were used. The specimens were scanned using both CBCT and micro-CT. The presence of facial canal dehiscence in the tympanic segment of the facial nerve (FN) was evaluated. A paired sample t-test was used for statistical analysis, with significance set at p < 0.05. Results Facial canal dehiscence was detected in 10 bones on micro-CT images, while 26 bones appeared intact. In contrast, CBCT images showed dehiscence in 25 bones, with 11 bones intact. Additionally, the mean dehiscence width was 3.469 mm (range: 1.577–8.921 mm) in micro-CT images, compared to 1.279 mm (range: 0.670–9.354 mm) in CBCT images. In the 10 bones where dehiscence was identified by both methods, the average width of the dehiscence measured 5.347 mm (range: 1.840–9.354 mm) in the CBCT images. The difference in measurements between CBCT and micro-CT was statistically significant (p < 0.05). Conclusions and significance The low resolution of CBCT was insufficient for visualizing the thin bony tissue lining the facial canal. These findings suggest that the frequency of facial canal dehiscence measured in preoperative CBCT images may be overestimated compared to actual anatomical conditions. These findings provide critical insights for preoperative evaluation and surgical planning in middle ear procedures.